Usefulness of High Resolution T2-Weighted Images in the Evaluation and Surveillance of Vestibular Schwannomas? Is Gadolinium Needed?. Issue 1 (January 2020) - Pizzini, Francesca B.; Sarno, Alessandro; Galazzo, Ilaria Boscolo; Fiorino, Francesco; Aragno, Anna M. R.; Ciceri, Elisa; Ghimenton, Claudio; Mansueto, Giancarlo
Abstract : Objectives: First aim of study was to compare the diagnostic accuracy of high resolution T2-WI (HRT2-WI) and gadolinium-enhanced T1-weighted image (Gd T1-WI) sequences in quantitative evaluation of vestibular schwannomas (VS). The second one was to determine through qualitative evaluation when Gd-injection should be recommended. Methods: Two observers in consensus retrospectively reviewed 137 magnetic resonance imaging (MRI) scans of patients with histological diagnosis of VS (33 women, 26 men), 116 with both HRT2-WI and Gd T1-WI. The examinations were subdivided in: surveillance (10), pretreatment (30), posttreatment (43), and posttreatment follow-up (33) studies. Quantitative evaluation was based on size measurement of the lesion. Structural details of the lesion, facial nerve course, and involvement of the fundus of the internal auditory canal were assessed for the qualitative evaluation in both sequences. Results: No statistically significant changes were demonstrated between size measurement in the HRT2-WI and Gd T1-WI ( p = 0.329). Sensitivity, specificity, and accuracy of HRT2-WI in the detection of lesional size were 90.4, 98.9, 92.5%, respectively. HRT2-WI was worse for characterization of structural details in pretreatment, posttreatment, and posttreatment follow-up examinations. HRT2-WI showed better or equal capability for all the groups in the demonstration of the facial nerve course. In the evaluation of the involvement of the fundus of the internal auditory canal, HRT2-WI showed worse results or had a complementary role for the posttreatment and posttreatment follow-up groups, while in the other groups was considered mainly equal or complementary. Only in the surveillance group, HRT2-WI was never worse for all the criteria. Conclusion: Results for quantitative evaluation were similar in both the sequences. Gadolinium injection can be avoided only in surveillance studies.